Wind turbine design parameters based on the wind speed of the area (SCIÉNDO INGENIUM, 2021)
In this study, the design parameters of horizontal axis type wind turbines were determined from the wind speed in the area. Theories on the distribution of speeds and pressures in the wind turbine rotor, the application of the momentum theory and Betz's law were used. the speed and power data of the wind turbine were directly measured using a prototype 1153 watt multi-blade wind turbine and measuring instruments such as: an anemometer, Card Logger 850023-SS; DC-AC voltmeter and ammeter with digital display operating temperature: -10 ° C a 65 ° C. The results show a direct effect of wind speed on the power of the wind turbine and the size of the blades. The maximum efficiency obtained in the wind turbine is 59.25%; the maximum efficiency in the wind turbine increases exponentially with a larger diameter of the blades.
Keywords: Wind turbines; design parameters; wind speed; multiple blades